Kajian Kelayakan Usahatani Jamur Tiram Putih (Pleurotus ostreatus) (Studi Kasus Pada UMKM Agro Jamur Lombok Kecamatan Gunungsari Kecamatan Lombok Barat) - Fadli, Fadli; Utama FR, Aeko Fria; Hidayati, Lilik (LPPM Universitas Mataram, 2025)
White oyster mushrooms are one of the alternative foods that can be produced by farmers to meet the food needs of the community. The purpose of this study was (a) to determine the costs incurred by farmers in white oyster mushroom farming activities, and (b) to determine the feasibility of white oyster mushroom farming in Lombok Agro Mushroom UMKM. This study uses a descriptive method, where data sources include primary data and secondary data. The number of respondents in this study was 3 people consisting of business owners and employees. The analysis tools in this study used the R / C Ratio and B / C Ratio. The results showed that the total cost incurred in this farming business was IDR 2,633,763, while the income obtained was IDR 6,000,000 and income was IDR 3,366,237. This white oyster mushroom farming business is feasible to run because the R / C Ratio value> 1 and the B / C Ratio value> 0 were obtained. The R / C Ratio value obtained in this white oyster mushroom farming business was 2.28 and the B / C Ratio value was 1.28.